Dampak Bantuan Sosial terhadap Kesejahteraan Sosial Ekonomi Masyarakat pada Masa Pandemi di Kota Bandung - Andini Gumanti; Ade Yunita Mafruhat (Bandung Conference Series: Economics Studies, 2022)
Abstract. Social assistance is a policy issued by the government to overcome inequality in society. The socio-economic welfare of the community during the pandemic is influenced by the impact of the social assistance provided. The purpose of this study is to analyze the impact of social assistance provided by the government on the level of socio-economic welfare of the community during the pandemic in the city of Bandung. The method used in this research is descriptive quantitative and analytical model, namely the Wilcoxon signed rank test model. Data collection techniques using questionnaires and the population of the people of Bandung City who received social assistance. The sampling technique used was random sampling technique. The results of this study indicate that the social assistance provided by the government has a significant impact on the socio-economic welfare of the community. In addition, according to the average value in the descriptive statistical analysis, it shows that the individual impact indicator after receiving the social assistance has the largest coefficient value so that it becomes the most dominant indicator in influencing the socio-economic welfare of the community during the pandemic in the city of Bandung. Abstrak. Bantuan sosial merupakan suatu kebijakan yang dikeluarkan oleh pemerintah untuk menanggulangi ketimpangan yang ada di masyarakat. Kesejahteraan sosial ekonomi masyarakat selama masa pandemi dipengaruhi oleh dampak dari bantuan sosial yang diberikan. Tujuan dari penelitian ini yaitu menganalisis dampak bantuan sosial yang diberikan pemerintah terhadap tingkat kesejahteraan sosial ekonomi masyarakat pada masa pandemic di Kota Bandung. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dan model analisis yaitu model Wilcoxon signed rank test. Teknik pengumpulan data menggunakan kuesioner dan populasi masyarakat Kota Bandung yang menerima bantuan sosial. Teknik penarikan sampel menggunakan teknik random sampling. Hasil dari penelitian ini menunjukkan bahwa bantuan sosial yang diberikan pemerintah memberikan dampak yang signifikan terhadap kesejahteraan sosial ekonomi masyarakat. Selain itu, menurut nilai rata-rata dalam analisis statistik deskriptif menunjukkan bahwa indikator dampak individual sesudah menerima bansos mempunyai nilai koefisien terbesar sehingga menjadi indikator paling dominan dalam pengaruh terhadap kesejahteraan sosial ekonomi masyarakat pada masa pandemi di kota bandung.